2013
DOI: 10.1590/s1806-83242013000400002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium ascorbate on the bond strength of silorane and methacrylate composites after vital bleaching

Abstract: Effect of sodium ascorbate on the bond strength of silorane and methacrylate composites after vital bleaching Abstract: We investigated the effect of sodium ascorbate (SA) on the microtensile bond strengths (MTBSs) of different composites to bovine enamel after vital bleaching with hydrogen peroxide (HP) or carbamide peroxide (CP). Thirty bovine incisors were randomly divided into five groups and treated with no bleaching application (control), 35% HP alone, 35% HP + 10% SA for 10 minutes (HP + SA), 16% CP alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 18 publications
2
31
0
4
Order By: Relevance
“…Already Güler et al [34] emphasize that the SA performance will vary according to the composition of the bond system. Türkün and Kaya [15] found that the resistance values obtained after the AS application are similar to bleached teeth with an interval of one week after bleaching and teeth restored immediately have low bond strength values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Already Güler et al [34] emphasize that the SA performance will vary according to the composition of the bond system. Türkün and Kaya [15] found that the resistance values obtained after the AS application are similar to bleached teeth with an interval of one week after bleaching and teeth restored immediately have low bond strength values.…”
Section: Discussionmentioning
confidence: 99%
“…Freire et al [30] claim that, in an appropriate concentration, SA 10% facilitates rapid elimination of residual peroxide to two minutes after the bleaching with HP 35%, while Güler et al [34] say that the application of this should give for about 10 minutes, time estimated also by Suneetha et al [3] However, Whang and Shin [29], say one minute would be enough for the agent›s action. Despite the differences, which may be due to the methodology used in each study, all these authors indicate that professionals can carry adhesive procedures after the bleaching procedure provided the correct protocol application to be followed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Previous research has shown that up to ten minutes' application of 10% sodium ascorbate is effective in increasing the shear bond of composite resin in bleached teeth by 15-35% carbamide peroxide. [12][13][14] Carbamide peroxide is the material commonly used for extra coronal bleaching on vital teeth. In intracoronal bleaching, the most commonly used material is 35% H 2 O 2 .…”
Section: Dental Journal (Majalah Kedokteran Gigi)mentioning
confidence: 99%
“…Most studies, which tested the effectiveness of AS in reversing compromised bond strengths, used carbamide peroxide at low concentrations [5,[7][8][9][10][11][12][13][14][15][16]20,21,25,[28][29][30]33]. It is possible that SA was more effective in teeth bleached with carbamide peroxide due the hydrogen peroxide releases a high oxygen concentration [37].…”
Section: Sodium Ascorbate Versus Bleaching Agent Typementioning
confidence: 99%